TERMINOLOGI MANUSIA BERDASARKAN DI DALAM AL-QUR’AN: Istilah Manusia dalam al-quran - Ahmad Farid; Siti Nurmalasari; Siti Mukhayaroh; Magfhfiroh, Latifatul (JURNAL ILMIAH RESEARCH STUDENT, 2023)
Abstract.Allah SWT created humans in this world as a manifestation of His existence as the Creator of all His creatures, leading to obedience and devotion in the form of worship. In the Qur'an there are three themes that focus on human designations, namely a). Al-Basyar, especially from a physical or biological perspective (b). Al-Nas, namely humans according to their social point of view, and (c) Al-Ins or Al-Insan, namely humans according to their position and character. By remembering the position of humans as kings on earth and servants of Allah SWT, humans are blessed with the power of reasoning, knowledge, and the ability to distinguish between right and wrong, thus making them more "perfect" than other creatures. Keywords: Al- insan, Al- Basyar, An- Nas Abstrak. Allah SWT menciptakan manusia di dunia ini sebagai wujud eksistensi-Nya sebagai Pencipta seluruh makhluk-Nya, menuju ketaatan dan pengabdian dalam bentuk ibadah. Dalam Al-Qur'an terdapat tiga tema yang fokus pada sebutan manusia, yaitu a). Al-Basyar, terutama dari segi fisik atau biologis (b). Al-Nas yaitu manusia menurut sudut pandang sosialnya, dan (c) Al-Ins atau Al-Insan yaitu manusia menurut kedudukan dan wataknya. Dengan mengingat kedudukan manusia sebagai raja di bumi sekaligus hamba Allah SWT, maka manusia diberkahi dengan daya nalar, ilmu pengetahuan, dan kemampuan membedakan mana yang benar dan mana yang salah, sehingga menjadikannya lebih “sempurna” dibandingkan makhluk lainnya. Kata kunci: Al- insan, Al- Basyar, An- Nas